Protein interactions within and between two F‐type type IV secretion systems. Issue 5 (12th August 2020) - Koch, Birgit; Callaghan, Melanie M.; Tellechea‐Luzardo, Jonathan; Seeger, Ami Y.; Dillard, Joseph P.; Krasnogor, Natalio
Abstract: Bacterial type IV secretion systems (T4SSs) can mediate conjugation. The T4SS from Neisseria gonorrhoeae possesses the unique ability to mediate DNA secretion into the extracellular environment. The N. gonorrhoeae T4SS can be grouped with F‐type conjugative T4SSs based on homology. We tested 17 proteins important for DNA secretion by N . gonorrhoeae for protein interactions. The BACTH‐TM bacterial two‐hybrid system was successfully used to study periplasmic interactions. By determining if the same interactions were observed for F‐plasmid T4SS proteins and when one interaction partner was replaced by the corresponding protein from the other T4SS, we aimed to identify features associated with the unique function of the N. gonorrhoeae T4SS as well as generic features of F‐type T4SSs. For both systems, we observed already described interactions shared by homologs from other T4SSs as well as new and described interactions between F‐type T4SS‐specific proteins. Furthermore, we demonstrate, for the first‐time, interactions between proteins with homology to the conserved T4SS outer membrane core proteins and F‐type‐specific proteins and we confirmed two of them by co‐purification. The F‐type‐specific protein TraHN was found to localize to the outer membrane and the presence of significant amounts of TraHN in the outer membrane requires TraGN . Abstract : Type IV secretion systems (T4SSs) are membrane‐spanning multiprotein complexes. We have analyzed protein interactions in the T4SSs from N. gonorrhoeae and from the E. coli F‐plasmid. The two systems are involved in secretion of DNA and conjugation respectively but both belong to the F‐type T4SSs. While interactions for conserved T4SS proteins were similar differences were observed in interactions between conserved T4SS proteins and F‐type specific proteins and in the interactions between F‐type specific proteins.